2016
DOI: 10.1007/s00109-016-1487-z
|View full text |Cite
|
Sign up to set email alerts
|

Delicaflavone induces autophagic cell death in lung cancer via Akt/mTOR/p70S6K signaling pathway

Abstract: Delicaflavone showed anti-lung cancer effects in vitro and in vivo. Delicaflavone induced autophagic cell death via Akt/mTOR/p70S6K signaling pathway. Delicaflavone did not show observable side effects in a xenograft mouse model. Delicaflavone may represent a potential therapeutic agent for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 41 publications
1
41
1
Order By: Relevance
“…Autophagy is known to be a self-degradative process that is important for balancing sources of energy at critical times during development, and in response to nutrient stress ( 32 ). Studies have demonstrated that autophagy is involved in a number of general processes, including proliferation, development, apoptosis and cell death ( 33 , 34 ). LC3BII, Beclin1 and P62 are closely associated with the formation of autophagosomes, serving as markers of autophagy ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is known to be a self-degradative process that is important for balancing sources of energy at critical times during development, and in response to nutrient stress ( 32 ). Studies have demonstrated that autophagy is involved in a number of general processes, including proliferation, development, apoptosis and cell death ( 33 , 34 ). LC3BII, Beclin1 and P62 are closely associated with the formation of autophagosomes, serving as markers of autophagy ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo anticancer effect of the total biflavonoids extract was evaluated according to previous method with slight modification [ 10 , 11 ]. Described briefly, the mouse xenograft model was established by injection of 2 × 10 6 LLC cells s.c. into the right armpit of six to eight-week old C57BL/6 male mice (18–22 g, obtained from the National Rodent Laboratory Animal Resource, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…A few components have been isolated from this plant genus, including flavonoids, lignans, polysaccharides, and so on [ 2 ], some of which have been reported to possess anti-diabetic, anti-inflammation, anti-oxidative, and anti-cancer activities [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Modern pharmacological studies showed that the ethanol extract of S. doederleinii could induce human nasopharyngeal carcinoma cell (CNE) apoptosis [ 5 ] and because of abundant biflavonoids, the ethyl acetate extract had more powerful anti-cancer activities than the ethanol extract for S. doederleinii [ 6 , 7 , 8 , 9 , 10 , 11 ]. Our recent studies demonstrated that the biflavonoids in S. doederleinii were concentrated mostly in the ethyl acetate extract, and the total biflavonoids could reduce the expression of antigen Ki67, decrease tumor microvessel density (MVD), and significantly inhibit the tumor growth, and did not show apparent oral acutetoxicity in healthy mice [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on various substances have reported that autophagy plays a paradoxical role in anti-tumor therapy. Induction of autophagic cell death by small molecules contributes to the enhancement of anti-tumor activity of chemotherapy or radiation therapy, whereas autophagy-dependent anti-apoptotic responses induced by chemotherapy have negative impacts on anti-tumor treatment through inhibition of the mTOR pathway 17,18 . To our best knowledge, no association between anti-tumor effects of PAM and autophagy has been reported.…”
mentioning
confidence: 99%